Effects of Commitment on Fear of Failure and Burnout in Teen Spanish Handball Players - González-Hernández, Juan; da Silva, Carlos Marques; Monteiro, Diogo; Alesi, Marianna; Gómez-López, Manuel (Frontiers in Psychology, 2021)
Under an observational, transversal and descriptive design, this study analyze the degree of adjustment of the perceptions of the fear of failure as a mediating variable of the estimated relationship between sporting commitment and the appearance of burnout in young handball players in a competitive context. The sample included a total of 479 youth category handball players (250 boys and 229 girls) selected to compete in the Spanish Regional Championships. The age range was 16 (40.1%) - 17 (59.9%) years old (M=16.60; SD=.50.) With regard to the years of experience variable, 85.4% stated that they have more than five years of experience at the federated handball player level. Using the Spanish version of Performance Failure Appraisal Inventory (PFAI), Inventory Athletes Burnout Revised (IBD-R), and Sport Commitment Questionnaire (SCQE). The correlation patterns evidence that commitment is negative and significantly associated with emotional exhaustion, depersonalization and fear of failure, and positive associated with reduced sense of personal accomplishment. In the standardized direct effect, negative and significant effects were observed between commitment and fear to failure, fear to failure with emotional exhaustion and depersonalization and on the contrary, a negative and significant effect was observed between fear of failure and reduced sense of personal accomplishment. Athletes evaluated reflect a positive psychological disposition, show pride in being selected and a high desire to show their sporting qualities. Despite the emergence of cognitive-emotional processes associated with fear of failure (e.g., shame, fear of criticism), this has been observed to protect the sense of self-fulfillment through sport effort, although it also impacts on further emotional exhaustion and loss of value of sport effort